The benefits of the C1 and C2 vertebrae derotation in patients with chronic cervical myofascial pain. A case report - Pop, Marius Sorin (PONS - medicinski časopis, 2017)
ABSTRACT Objective. The aim of this study was to present the case of a patient with chronic cervical pain and an elevated postural imbalance in the frontal plane. Method. The present case report was carried out in June 2017. The subjective assessment of the pain, the global postural assessment, the computerized baropodometry, the assessment of the walking and the biomechanics of the foot and functional tests (Fukuda, Romberg, VAD 2.7, Vasyli Medical and Sahrmann), were used to assess the postural imbalance. Results. The objective results were the immediate alignment of the cranium and underjaw to the central line of the body, a partial cancellation of the compensatory pathological curves from the area of the dorsal lumbar spine and the amplification of the laterality movement. The subjective result, as reported by the patient, was the absence of the previously felt discomfort at the active cranio-cervical mobility test, in the left laterality movement. Conclusion. The manual derotation of the C1 and C2 vertebrae resulted in efficient and long-term postural rehabilitation by canceling the fascial constraints and asymmetries at the base of the skull that maintained the postural syndrome, responsible in time for the onset of the symptomatology.